ChemInform Abstract: Exploring the Color of 3D Transition‐Metal Ions in Trigonal Bipyramidal Coordination: Identification of Purple‐Blue (CoO5) and Beige‐Red (NiO5) Chromophores in LiMgBO3 Host. Issue 13 (March 2016) - Tamilarasan, Subramani; Laha, Sourav; Natarajan, Srinivasan; Gopalakrishnan, Jagannatha
Abstract: Substitution of 3d transition metal ions for Mg in LiMgBO3 by the ceramic method leads to single phase materials LiMg1‐x Cox II BO3 (0 < x ≤ 1.0), LiMg1‐x Nix II BO3 (0 < x≤ 0.1), LiMg1‐x Cux II BO3 (0 < x ≤ 0.1), and LiMg1‐x Fex III BO3 (0 < x ≤ 0.1).